Revealing the Ecstasy of Communication upon using Tik Tok: A Virtual Ethnography in Palopo City, Indonesia - Wahyuni Husain; Saifur Rahman; Intan Soliha Ibrahim; Achmad Sulfikar (Profetik: Jurnal Komunikasi, 2025)
This research uses virtual ethnography to analyze TikTok usage patterns and the phenomenon of communication ecstasy among students in Palopo City. The qualitative field research method employed involves the use of questionnaires, interviews, observation, and documentation. A total of 53 students from universities in Palopo City participated in the questionnaire, and four were selected for further analysis through interviews. Data were analyzed using reduction techniques, presentation, and drawing conclusions. The results reveal that TikTok usage is prevalent among students, with daily use averaging over three hours per day. The purpose of use varies, including entertainment, information seeking, stress relief, hobby expression, and money-making. The phenomenon of communication ecstasy is evident in students' addiction to digital symbols like "like," "comment," "share," and "save." TikTok features enable students to immerse themselves in total simulation, blurring the lines between reality and virtuality, representation and reference, and facilitating the creation of simulacra and hyperreality. The implications suggest that TikTok is significantly altering communication patterns among students, leading to a shift from in-depth, meaningful interactions to more superficial, symbolic exchanges. This shift fosters a pseudo-environment where students can meticulously curate and project an idealized version of themselves, further obscuring the boundaries between authenticity and performance. As a result, the emphasis on visual storytelling and viral trends can lead to a culture of comparison and validation, potentially impacting students' self-esteem and social skills in the long term